(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
This article aims to analyze the impacts of discrimination on the remuneration of black teachers with higher education, according to the levels of basic and higher education in Brazil. Based on the microdata of the Continuous PNAD 2019, the wage determinants and the counterfactual decomposition of salaries were estimated, and the results prove wage inequality, predominantly gender and skin color discrimination among teachers. There is discrimination by upward skin color between elementary and high school for teachers, although there are no significant values in higher education. Compared to white teachers, black teachers suffer wage discrimination at all levels of education. Discrimination is the main responsible for the wage differences between black teachers and the other groups compared, which demonstrates that the mere acquisition of human capital and better professional insertion are not enough to break down the barrier of inequality to which teachers are inserted.